Nuclear magnetic resonance spectroscopy in environmental chemistry - Nanny, Mark A (Oxford University, 2014)
The text aims to provide a bench-mark for the current application of NMR spectroscopy to research problems in environmental science and technology, and also to demonstrate the diversity and breadth of environmental research problems that NMR spectroscopy can address.